Diversity analysis of indoor and outdoor fungal bioaerosols in UK households: a longitudinal study - Hemmings,S; Varaden,D; Barnes,J; Elmi,M; Skillern,A; Barratt,B; Mudway,I; Green,D; Kelly,F; Fisher,M (The Lancet Microbe, 2026)
BackgroundProlonged exposure to indoor fungal bioaerosols is a recognised risk factor for respiratory illness, particularly in damp and poorly ventilated housing. However, the diversity and seasonal variability of these communities are poorly understood. This study as part of WellHome, aimed to characterise the composition, diversity, and temporal dynamics of indoor fungal bioaerosols in urban UK homes compared with outdoor air, to inform future exposure baselines and policy development.MethodsIn this prospective, community-based observational study, 118 households were recruited across West London, UK, via community networks and partner organisations, prioritising families with children aged 5–17 years with asthma or allergies from diverse socioeconomic backgrounds. Sampling occurred between 3rd October 2022 and 14th June 2024. Participant data was collected via questionnaires completed by household members, capturing demographics, building characteristics, and respiratory health. Passive air samplers were deployed in living rooms for 28 days during two seasonal campaigns, with concurrent outdoor sampling at four fixed community sites. Fungal bioaerosols were identified by ITS2 amplicon sequencing and quantified using broad-range qPCR targeting the 18S rRNA gene. Diversity indices and temporal dynamics were analysed using ecological statistics and generalised additive models.Findings118 households were enrolled, comprising 504 residents (263 female, 237 male, 4 not reported). Of these, 104 households completed both seasonal campaigns and 14 completed one, yielding 262 air samples (222 indoor, 40 outdoor). DNA was successfully recovered from all samples, identifying 2,027 fungal genera. Indoor environments showed significantly higher richness (mean 646 vs 495 ASVs; p<0.0001) and Shannon diversity (4.21 vs 3.53; p<0.0001) than outdoors. Community composition differed markedly (PERMANOVA p<0.0001), with Penicillium, Aspergillus, and Wallemia enriched in